Comparative efficacies of intratympanic steroid administration and classic therapy in the management of idiopathic sudden sensorineural hearing loss - Gümüşsoy, Murat; Burak Arslan, İlker and Çukurova, İbrahim (ENT Updates, 2013)
Objective: Sudden hearing loss is a sensorineural hearing loss with an unknown etiology at ≥30 dB which appears in 3 days or within a shorter period of time and obstructs three successive frequencies. Our objective in this study is to assess the effectiveness of the combination of classic therapy and intratympanic steroid treatment in the management of idiopathic sudden sensorineural hearing loss. Methods: One hundred and forty patients diagnosed with idiopathic sudden sensorineural hearing loss in our clinics between February 2010 and June 2012 were separated into 2 groups. Seventy-six patients [37 women (48.68%) and 39 men (51.32%)] with a mean age of 45.1±14.16 years managed with a combination of classic sudden hearing loss and intratympanic steroid treatment (Group 1) and 64 patients [34 women (53.18%) and 30 men (46.82%)] with a mean age of 47.6±17.74 years managed with only classic sudden hearing loss treatment (Group 2) were included in the study. One month after the study, pure-tone averages and speech discrimination scores of the patients were compared with those obtained 1 month before the treatment. Results: Pure-tone average of the intratympanic-steroid treatment group was found to be 68.28 dB before the treatment where in the other group it was 67.21 dB without any statistically significant difference between groups. When followed-up 1 month after the therapy, pure-tone average was found to be 33.52 dB in the intratympanic steroid treatment group and 44.46 dB in the classic therapy group with a statistically significant intergroup difference. Gain was up to 34.76 dB in the intratympanic steroid treatment group whereas in the classic therapy group, the difference was 22.75 dB which was found to be statistically significant (p<0.05). Conclusion: When treating idiopathic sudden hearing loss, intratympanic steroid treatment which was combined with sudden hearing loss treatment protocol tends to yield significant hearing gain when compared with the classic combined treatment.